The Relationship Between BMI And Neutrophil/Lymphocyte Ratio in Non-critical Hospitalized Patients With Coronavirus Disease 2019 (Bangladesh Journal of Medicine, 2022)
Background: People with obesity may be adversely affected by Coronavirusdisease 2019 (COVID-19). The objective of the study was to assess the clinical and biochemical characteristics of non-critical hospitalized patients of COVID-19 with obesity.Methods: This cross-sectional observational study was done among 88 non-critical hospitalized patients of COVID-19 [age: 50.0 (33.50-60.0) years, median (IQR); m/f: 36/52). The severity of COVID- 19 at diagnosis was determined by WHO interim guidance on COVID-19, 2000, and obesity was defined by a body mass index of 25 kg/m2. Clinical and biochemical information at diagnosis were collected in a data sheet.Results: Around 34% of the patients had obesity. Baseline characteristics and clinical features were statistically similar between obese and non-obese patients (NS for all). Among biochemical features, only total leukocytes (p=0.007), absolute neutrophils count (p=0.001), and neutrophils/ lymphocytes ratio (p=0.002) were significantly lower in obese patients than non-obese patients. Body mass index (BMI) had significant negative correlations with total leukocytes (r=-0.318, p=0.005), absolute neutrophil count (r=-370, p=0.001) and neutrophils/lymphocytes ratio (r=-0.349, p=0.002) in the study population.Conclusion: BMI had inverse associations with total leukocytes, absolute neutrophil count, and neutrophil/lymphocyte ratio among non-critical hospitalized patients with COVID-19.Bangladesh J Medicine 2022; 33: 36-42